The G20 at a crossroads: The future of global governance - Dennis J. Snower (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The G20 is at a crossroads. It can retreat to a reaffirmation of nationalisms or commit to a new form of multilateralism, guided by the primacy of social prosperity and the principle of subsidiarity. The G20 has traditionally focused on economic policy issues - economic growth and financial stability. This is appropriate as along as social progress is closely tied to economic progress, for then the achievement of material prosperity will promote human flourishing. But when economic and social progress becomes decoupled - as we commonly observe through growing income disparities, growing disempowerment and disintegrating social affiliations - then an exclusive preoccupation with economic policy issues is unlikely to quell the widespread public discontent. On this account, it is appropriate for the G20 objectives to be broadened to include resilient, inclusive and sustainable prosperity. This wider conception of human needs calls for a new worldview to underlie G20 policymaking, one that generates social acceptance for multilateral cooperation in tackling multilateral problems, while allowing different countries to nourish different national, cultural and religious identities.
Keywords: F5; H7; 330; G20; governance; international cooperation; empowerment and solidarity